STRATEGI PENGEMBANGAN KEGIATAN KEAGAMAAN ANAK USIA DINI DI TK HARAPAN IBU TANAH MAS BANYUASIN - Nyimas Nurrohma (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2017)
This study found that first, the kindergarten strategy in developing the early childhood religious activities in Harapan Ibu Tanah Banyuasin kindergarten was pursued by establishing the development of the religious activities of the AUD that wanted to be internalized, establishing the form of its assessment, planning daily habituation along with its religious activity programs, applying Development of religious activities, awaken to all teachers of important roles and responsibilities in achieving the goal of developing religious activities in early childhood, as well as cooperating with the guardian of students in the development of early childhood religious activities in the kindergarten. Then the second discovery, finding the learning method used that is using exemplary methods, habituation, attention and supervision, methods of advice, game methods and story methods. Then the third finding, The supporting factor in developing the early childhood religious activities in kindergarten Harapan Ibu Tanah Mas Banyuasin is the awareness of the classroom teachers on the importance of the development of early childhood religious activities, the presence of good facilities and infrastructure, the establishment of harmonious cooperation between The school and parents in terms of developing the early childhood religious activities, the attention of both teachers and parents, the happiness of learners as well as inhibiting in developing the early childhood religious activities of the absence of awareness of the teacher on the importance of the development of religious activities, Lack of facilities and infrastructure, no good cooperation between parents and teachers, the lack of attention of parents and teachers in terms of religious activities of early childhood and the last absence of the happiness of learners in following the religious activities that take place.